Teachers’ Understanding of STEM Education in Secondary Schools: A Systematic Literature Review and Bibliometric Mapping Towards SDG 4 - Rinie Pratiwi Puspitawati; Pramita Yakub; Rooselyna Ekawati; Muhammad Zahrudin Afnan (Journal of Current Studies in SDGs, 2027)
Objective: The study aims to map research on teachers’ STEM understanding in secondary education, identify major themes and emerging trends, and examine research gaps related to teacher competence and STEM implementation across junior and senior secondary education. Method: A systematic literature review and bibliometric analysis were conducted on studies published between 2010 and 2025. Following the PRISMA framework, 884 records were initially identified, of which 144 studies met the inclusion criteria. The analysis covered keyword co-occurrence, thematic evolution, research density, geographical distribution, and qualitative synthesis of the selected studies. Results: The findings show that research has shifted from early attention to teachers’ perceptions, attitudes, knowledge, and preparedness toward STEM pedagogical content knowledge, interdisciplinary competence, professional development, inquiry, engineering design, creativity, sustainability, and classroom implementation. STEM education, teacher training, professional development, and pedagogical content knowledge emerged as central themes. However, substantial gaps remain between teachers’ STEM awareness, conceptual understanding, pedagogical readiness, and actual classroom implementation. Comparative studies between junior and senior secondary teachers also remain limited. Novelty: The study provides an integrated systematic and bibliometric mapping of teachers’ STEM understanding across secondary education levels and highlights teacher competence as a potential bridge between quality education and sustainable development, particularly in relation to SDG 4, SDG 9, and SDG 13.